2019
DOI: 10.3139/o999.04022019
|View full text |Cite
|
Sign up to set email alerts
|

UV Surface Treatment of Polycarbonate for Ad-hesion Improvement to Liquid Silicone Rubber (LSR)

Abstract: The adhesion of self-adhesive liquid silicone rubbers to thermoplasts is only possible for a few selected material combinations without a surface pretreatment. A UV pretreatment is effective for polycarbonate and short irradiation periods are sufficient. To clarify the required irradiation conditions that result in an improvement of adhesion, the varying irradiation conditions were assessed. FTIR-ATR spectroscopy was used for surface analysis to characterize the change in the polymer surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Similar to other activation methods, the degradation of the crosslinker in silicone components during artificial aging also plays a role in diminishing adhesive properties [23,24]. Additionally, it could be postulated that the radicals generated from UVC irradiation form more robust bonds with the silicone components, resulting in more stable properties against temperature and humidity [18]. As a result of sterilization, the values for both thermoplastics also dropped (Figur 9).…”
Section: Peeling Testmentioning
confidence: 87%
See 1 more Smart Citation
“…Similar to other activation methods, the degradation of the crosslinker in silicone components during artificial aging also plays a role in diminishing adhesive properties [23,24]. Additionally, it could be postulated that the radicals generated from UVC irradiation form more robust bonds with the silicone components, resulting in more stable properties against temperature and humidity [18]. As a result of sterilization, the values for both thermoplastics also dropped (Figur 9).…”
Section: Peeling Testmentioning
confidence: 87%
“…Simultaneously, a decrease in the region corresponding to the two unsaturated bonds, trans-1,4 (967 cm −1 ) and vinyl-1,2 (911 cm −1 ) C=C, was evident as the UVC irradiation time increased [15][16][17]. The nitrile, aromatic, and aliphatic groups appeared to be less impacted due to the higher binding energy of the C≡N bond, which exceeds the energy of UVC irradiation [18].…”
Section: Ftir Analysis Of Samples After Uvc Irradiationmentioning
confidence: 98%
“…In general, high-energy electromagnetic radiation can generate new functional groups on the surface of the polycarbonate, which have a positive effect on wettability and adhesion [ 10 , 11 , 12 , 13 ]. Our studies [ 14 ] showed that UVC irradiation of polycarbonate can generate a strong adhesion to standard self-adhesive LSR where initially there is none. It was found that the effect of adhesion promotion when using ozone-generating UVC lamps depends on the irradiation dose, which must be slightly higher with increasing irradiation distance.…”
Section: Introductionmentioning
confidence: 99%